SoxE proteins are differentially required in mouse adrenal gland development. - Reiprich, Simone; Stolt, Claus; Wegner, Michael; et al. (Molecular Biology of the Cell, 2008)
Sry-box (Sox)8, Sox9, and Sox10 are all strongly expressed in the neural crest. Here, we studied the influence of these closely related transcription factors on the developing adrenal medulla as one prominent neural crest derivative. Whereas Sox9 was not expressed, both Sox8 and Sox10 occurred widely in neural crest cells migrating to the adrenal gland and in the gland itself, and they were down-regulated in cells expressing catecholaminergic traits. Sox10-deficient mice lacked an adrenal medulla. The adrenal anlage was never colonized by neural crest cells, which failed to specify properly at the dorsal aorta and died apoptotically during migration. Furthermore, mutant neural crest cells did not express Sox8. Strong adrenal phenotypes were also observed when the Sox10 dimerization domain was inactivated or when a transactivation domain in the central portion was deleted. Sox8 in contrast had only minimal influence on adrenal gland development. Phenotypic consequences became only visible in Sox8-deficient mice upon additional deletion of one Sox10 allele. Replacement of Sox10 by Sox8, however, led to significant rescue of the adrenal medulla, indicating that functional differences between the two related Sox proteins contribute less to the different adrenal phenotypes of the null mutants than dependence of Sox8 expression on Sox10. © 2008 by The American Society for Cell Biology.
UnivIS-Import:2015-03-09:Pub.2008.med.IB.LPCIPDBI.soxepr